Cultivating Cultural Awareness in Early Childhood: The Role of Batik Tulis in Preserving Local Heritage - Umi Rofiqoh , Fitria; Muthmainnah (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
This study explores the efficacy of batik tulis (written) for introducing and preserving local cultural heritage in early childhood education. Conducted at TK Batik PPBI Yogyakarta, this qualitative research utilized observations, interviews, and documentation to assess how batik-making activities influence cultural awareness among preschoolers. Results reveal that the batik introduction process familiarizes children with this local art form and instills a profound appreciation for cultural traditions. The educational methodology was designed to be age-appropriate and interactive, integrating safety measures and encouraging active participation throughout all stages of learning—from understanding the cultural significance of batik to hands-on crafting. The findings highlight the pivotal role of integrating cultural elements into early education to cultivate a long-lasting appreciation and knowledge of local heritage. This approach not only aids in cultural preservation but also enriches the educational experience, fostering a generation that values and understands its cultural roots. However, the study's limited scope, focused on a single educational setting, suggests the need for further research. Future studies should aim to replicate and validate these findings across various educational contexts to understand better the effectiveness and scalability of integrating cultural education in early childhood settings. These insights advocate for educational reforms recognizing and utilizing local cultural heritage as a fundamental component of comprehensive educational strategies, potentially influencing broader pedagogical practices.